Fostering Creativity with ChatGPT in Requirements Engineering Education: An Academic Experience - Costa, Marcos; Lima, Márcia; Meireles, Maria; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.15260, 2025)
In the context of Software Engineering education, the Requirements Engineering (RE) phase plays a key role, as it directly influences the quality of the final product. Among the key competencies to be developed in this process is creativity, which is essential for developing innovative solutions that meet user needs. Since the emergence of Large Language Models (LLMs), their use has become more widely adopted in various stages of software engineering (SE), including RE. Thus, stimulating creative thinking through the use of LLMs in the classroom is a promising strategy for preparing future professionals capable of facing complex challenges and proposing original solutions from the early stages of software development. Based on this, the present study investigated the relationship between the use of LLMs, specifically ChatGPT-3.5, and the stimulation of creativity during software RE. For this purpose, we conducted a study with 42 students enrolled in an introductory SE course. Participants did a creative requirements generation activity using the Brainwriting technique, conducted in two stages: the first without the support of tools, and the second with the use of ChatGPT. The requirements generated in both stages were evaluated based on four dimensions from the Torrance Test of Creative Thinking (TTCT): fluency, flexibility, originality, and elaboration. The results showed that using ChatGPT helped increase the number of ideas, the variety of categories covered, the level of detail, and, in many cases, the originality of the requirements. Despite this, it also highlighted limitations, such as the need for intensive filtering of the generated requirements and the superficiality of some proposals. These findings reinforce the potential of LLMs, when critically mediated, as a pedagogical tool to foster creative and reflective skills in the training of future software engineers.